(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
Respecting cultural citizenship is one of the primary virtues which need to be promoted in order to ensure the cultural rights of the individual, seen as the foundation of universal peace. To do so, it is necessary to question the traditional boundaries between art and society, allowing for a deeper reflection on the social role of art (Berleant, 2022). Added to this idea is another major element: civic "availability," or the willingness to "give time" to the appreciation of current artistic practices, characterized by constant novelty. This involves capturing – in an era of unprecedented pace of life – the "investment of the receiver," or the act of "putting one’s psychological energy into the activity of receiving a work of art" (Everaert-Desmedt, 2012). How then can we reconcile these dimensions in our era marked by an ever-increasing sense of acceleration? To answer this question, this article explores the theoretical foundations of "aesthetic engagement" (Berleant, 2022), before examining the limits of such engagement in a context of "time crisis" (Revault d’Allonnes, 2013). Additionally, this paper discusses the individual’s ability to "give oneself time" (Adrianssens and Montjotin, 2024) as a personal decision essential to the emergence of the "cultural citizen." Finally, I attempt to clarify how this approach fosters societal dynamics, with a particular emphasis on their educational implications.